2018
DOI: 10.1002/jbio.201700394
|View full text |Cite
|
Sign up to set email alerts
|

Probing endogenous collagen by laser‐induced autofluorescence in burn wound biopsies: A pilot study

Abstract: The focus of the current study was to interrogate the predictive potential of laser-induced autofluorescence (LIAF) by objectively assessing collagen synthesis in burn wound granulation tissues ex vivo. Prior grafting, granulation tissues (20 samples) following burn injury were collected from 17 subjects of age range 18 to 60 years with patient/donor consent and the corresponding autofluorescence spectra were recorded at 325 nm He-Cd laser (≈2 mW) excitations. The resulting endogenous collagen intensity from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…The application of autofluorescence measurements in clinical research was boosted by advances in light delivery and collection via fiber‐optic systems, which facilitated the development of optical techniques for non‐ and minimally invasive measurements of tissues, including in endoscopic and catheter procedures . The clinical potential and feasibility of autofluorescence measurements for in vivo clinical diagnosis have been demonstrated in a number of studies, either employing steady‐state , and/or time‐resolved autofluorescence measurements . Steady‐state autofluorescence intensity or emission spectroscopy have been widely employed in clinical diagnostic research and are by far more intensively exploited compared to time‐resolved measurements, mainly due to the simplicity and typically lower cost of the instrumentation involved.…”
Section: Introductionmentioning
confidence: 99%
“…The application of autofluorescence measurements in clinical research was boosted by advances in light delivery and collection via fiber‐optic systems, which facilitated the development of optical techniques for non‐ and minimally invasive measurements of tissues, including in endoscopic and catheter procedures . The clinical potential and feasibility of autofluorescence measurements for in vivo clinical diagnosis have been demonstrated in a number of studies, either employing steady‐state , and/or time‐resolved autofluorescence measurements . Steady‐state autofluorescence intensity or emission spectroscopy have been widely employed in clinical diagnostic research and are by far more intensively exploited compared to time‐resolved measurements, mainly due to the simplicity and typically lower cost of the instrumentation involved.…”
Section: Introductionmentioning
confidence: 99%
“… 45 An Indian study focused on laser‐induced autofluorescence as a noninvasive objective tool to measure the endogenous collagen levels in burn wound granulation tissues ex vivo. 46 A group from California investigated the use of a fiber‐based, multispectral fluorescence lifetime imaging system to nondestructively monitor changes in mechanical properties of collagen hydrogels caused by controlled application of cross‐linking agents. 47 The authors observed strong and specific correlations between fluorescence lifetime and the storage or Young's moduli of the gels.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, Lutz et al analyzed collagen synthesis and structure using the signals second harmonic generation (SHG) and fluorescence lifetime of collagen autofluorescence by multiphoton laser scanning microscope 45 . An Indian study focused on laser‐induced autofluorescence as a noninvasive objective tool to measure the endogenous collagen levels in burn wound granulation tissues ex vivo 46 . A group from California investigated the use of a fiber‐based, multispectral fluorescence lifetime imaging system to nondestructively monitor changes in mechanical properties of collagen hydrogels caused by controlled application of cross‐linking agents 47 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation